Third molar impaction position in Peruvian adults - Palomares Uchuya, Saly Lizbeth (2021)
Objective. To determine the position of the third molars in patients treated in a diagnostic imaging center in Lima during the period 2017-2020. Methodology. An observational, descriptive,  cross-sectional  and  retrospective research was carried out; which consisted of a sample of 253 panoramic radiographs of patients treated in a private radiological center. The position of the lower third molars, the depth of impact, and their impaction position in relation to the mandibular ramus were evaluated using the Pell and Gregory classification; as well as the Winter classification. The data were analyzed in the statistical package SPSS vs. 26. Outcome. It was observed that the vertical and mesioangular position were the most common  with 14.6%  and 13.2%; respectively. Type I and II according to Pell and Gregory was the most common with values of 15.4%  and 14.4%; as well as, class B with 15.4%. Conclusion. The vertical and mesioangular impaction position, type B and class II were the most frequent for the lower third molars.